Anthropomorphic Original Gripper with Two-Finger Tests during Grasping Objects with Varied Shapes - Ionel Staretu; Marian Bolboe (Research and Developments in Engineering Research Vol. 2, 2023)
The study discusses theoretical and experimental findingson an original anthropomorphic gripping concept. This gripper is fairly basic compared to other anthropomorphic grippers, but it has the benefit of good performance in terms of grasping options and extremely inexpensive production costs. The human hand, which can grasp objects using just two fingers, served as inspiration. The anthropomorphic gripper under consideration has two fingers with two phalanxes each and is based on a new mechanism with articulated bars. The gripping mechanism’s kinematic analysis reveals the optimal displacement in the translational coupling, which has been experimentally validated. By attaching clamping jaws to each phalanx, the gripping possibilities were expanded. The clamping jaws are connected with spherical couplings, allowing them to catch objects with any type of surface. We emphasize the importance of safe use of two-fingered anthropomorphic grippers in various applications by conducting gripping tests with various objects. The gripper’s innovative mechanical structure ensures minimum gripping conditions, while the complexity of the objects that can be gripped makes it suitable for use in robots. The paper presents several examples of grasping parts of different shapes, stiffnesses and sizes, which validate the technical solution realized in practice.